Behavioral Experiments in Single-Agent Operational Problems (2018)
This chapter begins with an introductory section that explains the need for experimental research in humanitarian operations. It then describes the methodology of behavioral experiments, emphasizing randomization and induced valuation. This is followed by a survey of single-agent behavioral experiments in operations management, focusing on newsvendor and forecasting studies. The chapter provides normative benchmarks for prototypical newsvendor and forecasting problems, shows how individuals’ behaviors deviate from such benchmarks and provides suggestions to extend the surveyed results to humanitarian operations. The chapter concludes with a summary of the work.